A Review On Recovering Waste Heat From Condenser Of Domestic Refrigerator - Kalpesh Nagmoti, Prof. Anil Dube, Tanmay Patil, Nitesh Medhane, Yogesh Mahapure, (International Journal of Scientific Research and Management (IJSRM), 2015)
To review the energy savings associated with improved utilization of waste heat from a domestic refrigerator. Domestic refrigerators may be operating continuously to maintain proper food storage condition. The continuous operation of this equipment accounts more electrical energy consumption. So it is that a significant and concrete effort should be made for conserving energy through waste heat recovery. A significant amount of waste heat is rejected by the condensers of refrigerator. So an attempt has been made to utilize waste heat from the condenser of a refrigerator. Practical uses of waste heat from the domestic refrigerators are typically to space heating and water heating in minimum constructional maintenance and running cost. A cabin was installed on a domestic refrigerator with condenser coils of refrigerator serving as heating coils inside the cabin. Known quantity of water was heated by the condenser coils (due to convection currents) thereby increasing the overall COP of the refrigerator. Besides, the refrigerator may be used as conventional refrigerator by keeping the cabin door open in case of absence of heat sink.